2019
DOI: 10.1002/jcb.29015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of liraglutide on expression of CTGF and BMP‐7 in induced diabetic nephropathy

Abstract: Introduction Diabetic nephropathy (DN) is one of the critical complications of diabetes mellitus and the main cause of chronic renal dysfunction. The pathogenic mechanism causing the disease remains unclear and there is a lack of effective treatment methods so novel strategies are needed for DN management. The aim of this study, therefore, is to evaluate the effect of liraglutide as glucagon‐like peptide‐1 analogue and its underlying mechanisms on induced DN in rats Materials and Methods Sixty rats were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This study indicated that liraglutide combined with Jinlida could improve vascular endothelial function in T2DM patients by reducing ET-1 and elevating NO. This is mainly because liraglutide can protect the blood glucose regulation function of the remaining islet cells, improve the insulin resistance of diabetic patients, reduce or relieve the toxic effect caused by hyperglycemia, thus relieving the oxidative stress reaction in the body, maintaining the normal function of vascular endothelium, promoting NO expression, inhibiting endothelial cell apoptosis and inducing proliferation, thereby reducing vascular endothelial damage and maintaining a stable endothelial environment [20][21][22][23][24][25][26]. In addition, this study found that T2DM patients receiving liraglutide treatment based on Jinlida would not increase the incidence of adverse reactions, suggesting that combination therapy is relatively safe.…”
Section: Groupsmentioning
confidence: 99%
“…This study indicated that liraglutide combined with Jinlida could improve vascular endothelial function in T2DM patients by reducing ET-1 and elevating NO. This is mainly because liraglutide can protect the blood glucose regulation function of the remaining islet cells, improve the insulin resistance of diabetic patients, reduce or relieve the toxic effect caused by hyperglycemia, thus relieving the oxidative stress reaction in the body, maintaining the normal function of vascular endothelium, promoting NO expression, inhibiting endothelial cell apoptosis and inducing proliferation, thereby reducing vascular endothelial damage and maintaining a stable endothelial environment [20][21][22][23][24][25][26]. In addition, this study found that T2DM patients receiving liraglutide treatment based on Jinlida would not increase the incidence of adverse reactions, suggesting that combination therapy is relatively safe.…”
Section: Groupsmentioning
confidence: 99%
“…diabetic nephropathy (dn) is a type of severe complication of diabetes mellitus (dM) and is the main cause of chronic kidney disease (1). Various of mechanism are reported to be involved in the pathogenesis and development of dn, such as hyperglycemia, oxidative stress (2), mitochondrial dysfunction (3), endoplasmic reticulum stress, chronic inflammation and abnormal autophagy (4).…”
Section: Introductionmentioning
confidence: 99%